Participatory learning for sustainable livestock management: the impact of field school in Tasikmalaya - Kamal, Ruhyana; Nursoba, Farid; Matin, Asep (Galuh International Journal of Community Service and Development, 2025)
Tasikmalaya Regency, with its abundant agricultural potential, is a strategic location for the Integrated Farming System Development Project in the Highlands (UPLAND). This project aims to increase agricultural productivity through a holistic and integrated approach, focusing on developing location-specific, export-oriented agricultural commodities. The 1st Batch of Livestock Business Management Field School was held to improve the knowledge and skills of farmers in livestock business management. The method used was participatory learning based on experience, with 80% of the time spent on direct practice in the field. The evaluation results showed an increase in the average score of participants from 69.60 to 84.40, proving the effectiveness of the Field School in improving knowledge and skills. The practice of cultivating Green Forage was the most popular activity. The Field School has proven to be effective in improving the knowledge and skills of farmers in various agricultural sectors, in line with previous research. This activity ended with the preparation of a follow-up plan by participants to apply the knowledge gained. However, the limited duration of the training and the evaluation that was limited to measuring knowledge were noted. For the future activity, a more comprehensive evaluation and development of a more in-depth training module are needed.